Polymeric nanocapsules via interfacial cationic photopolymerization in miniemulsion. (14th March 2018) - Artusio, Fiora; Bazzano, Marco; Pisano, Roberto; Coulon, Pierre-Eugène; Rizza, Giancarlo; Schiller, Tara; Sangermano, Marco
Abstract: The synthesis of polymeric nanocapsules by means of miniemulsion cationic polymerization has been investigated here. The core-shell structure was obtained by confining the reaction at the interface between continuous and dispersed phase of an oil-in-water miniemulsion. This hallmark also allows to carry out the cationic UV-activated polymerization of a vinyl monomer, namely triethylene glycol divinyl ether, in water. The study firstly focused on formulation design. Various kinds of surfactant were examined and SDS provided optimal miniemulsion stability. Moreover, several amounts of surfactant, photoinitiator and oil were tested to optimize formulation composition. Nanocapsules were successfully synthesized and their average size, dimensional distribution, surface zeta potential, stability over time, morphology and thermal behavior were explored. Then, processing conditions, namely irradiation time and sonication time, were investigated. Results highlighted the possibility to design nanocapsule dimension by acting on ultrasound exposure time and a minimum size of 200 nm was identified. Graphical abstract: Nanocapsules are synthesized via UV-activated cationic polymerization of triethylene glycol divinyl ether. Such reaction is confined at the interface between the aqueous continuous phase and the oily dispersed phase of a miniemulsion. Nanocapsule size, stability against aggregation, morphology, thermal transitions and surface zeta potential are analyzed according to formulation design and processing conditions. Highlights: Interfacial confinement allowed cationic polymerization to occur in aqueous media. Stable nanocapsules dispersions were obtained by choosing proper surfactant. Core-shell structure was demonstrated by TEM experiments. Design of nanocapsule size was achieved by tuning process conditions.